Upregulation of OTUD7B (Cezanne) Promotes Tumor Progression via AKT/VEGF Pathway in Lung Squamous Carcinoma and Adenocarcinoma - Lin, Dan-dan; Shen, Yang; Qiao, Shu; Liu, Wen-wen; Zheng, Lishuang; Wang, Ya-nan; Cui, Naipeng; Wang, Yun-fan; Zhao, Shuli; Shi, Jian-hong (Frontiers in Oncology, 2019)
OTUD7B, a multifunctional deubiquitinylase, plays essential role in inflammation and proliferation signals. However, its function in lung cancer remains largely unknown. The aim of this study was to evaluate the prognostic significance of OTUD7B in patients with lung adenocarcinoma and squamous carcinoma and to characterize its molecular mechanisms in lung cancer progression and metastasis. Two tissue microarrays containing 150 pairs of lung squamous carcinoma and matched adjacent non-cancer tissues and one tissue microarray containing 75 pairs of lung adenocarcinoma and adjacent non-cancer tissues were included and immunohistochemical staining was performed to assess the clinical relevance of OTUD7B in non-small cell lung cancer. OTUD7B is highly expressed in both lung squamous carcinoma and adenocarcinoma and correlates with a worse prognosis. MTT proliferation, colony formation, migration and invasion assays and immunoblotting assay in NCI-H358 and A549 cell lines suggested that OTUD7B enhances EGF-induced Akt signal transduction and promotes lung cancer cell proliferation and migration. Immunohistochemical staining of large-scale lung cancer subjects (171 cases) revealed positive correlation of OTUD7B and VEGF expression. ELISA and tube formation assay revealed OTUD7B promotes VEGF production and angiogenesis. NCI-H358 tumor model demonstrated OTUD7B is required for lung tumour progression by facilitating activation of Akt signaling. These findings collectively identified OTUD7B as an independent predictive factor for the prognosis of non-small cell lung cancer and revealed OTUD7B promotes lung cancer cell proliferation and metastasis via Akt/VEGF signal pathway.